[PP.04.05] ACCELERATED DEVELOPMENT OF IMMUNE CELLS IN CHILDREN WITH PRIMARY HYPERTENSION. (September 2016) - NIEMIRSKA, A.; Obrycki, L.; Michalkiewicz, J.; Gackowska, L.; Kubiszewska, I.; Klosowski, M.; Litwin, M.
Abstract : Objective: Immune system plays a role in pathogenesis of primary hypertension (PH) and activation of immune cells is associated with subclinical hypertensive arterial injury. One of the markers of maturation of immune cells is increased number and percentage of memory cells. We hypothesized that children with PH have faster maturation of immune cells. Design and method: The distribution of peripheral T cell subsets (CD4+ and CD8+) expressing CD45 common leukocyte antigen (CD45Ag) isoforms: CD45RA (naive cells), CD45RO (memory cells) and CD31 (pecam-1, a marker of early thymic emigrants) was evaluated by three-color flow cytometry in a group of 11 PH adolescents and 16 healthy, age matched controls. Results: Hypertensive children had higher proportion of "memory" CD8 cells (CD8/CD8RO+) than their healthy counterparts (17.0 range: 11.9–23.8 vs 10.9 9.1–14.1; p = 0.03), lower of CD8/CD8RA+ cells (72.3 range: 66.5–81.9 vs 81.6 77.4–84.3; p = 0.05), and lower CD8RA/CD8RO+ ratio than the controls (5.1 range: 2.7–6.9 vs 7.4 5.5–8.9; p = 0.028). Percentage of CD4 and CD8 T bearing "naive" or "memory" phenotype correlated with brachial and aortic pulse pressure. Additionally, CD8RA/RO+ ratio was associated with pulse pressure (p = 0.03, r = −0.337) and aortic pulse pressure (p = 0.03, r = −0.384). There was also negative correlation of percentage of CD4/CD31+ with both absolute and standardized values of carotid wall cross sectional area (p = 0.01, r = −0.433 p = 0.016, r = −0.410, respectively). Conclusions: Adolescents with PH present subtle alterations in maturation of immune system manifested by: a) the decreased number of early thymic emigrants within CD4+ T cell suggesting accelerated thymic senescence, b) the increased population of more mature cells expressing "memory" markers, c) the associations with indirect indices of arterial stiffness and carotid artery remodelling and d) shift towards "memory" phenotype in T cells. Altogether these findings indicate that early stage of human primary hypertension and arterial remodelling may be related to certain defects in T cell development that result in accelerated maturation and senescence of immune system.